THEORY AND PRACTICE IN THE DEVELOPMENT OF ACCOUNTING. - Spiller, Earl A. (The Accounting Review, 1964)
In any attempt to investigate accounting in search of general principles, one is immediately impressed by the difficulty in determining exactly what accounting is. For anyone looking at accounting is confronted with two rather distinct well-springs of accounting thought. In one case accounting is a practical art attempting to record, classify, and summarize certain facts and events relating to business operations. On the other hand, accounting can be viewed as a theory of financial communication, founded on assumptions and containing logically derived and internally consistent conclusions. The fact is that there has actually been a dual or concurrent development in accounting. While accounting was developing as a practical art, it was also evolving a body of theoretical knowledge. The practical development can be traced back five hundred years, the theoretical evolution is of much more recent vintage. This paper will discuss the differences between the theoretical and practical development of accounting and why these differences exist.